2005
DOI: 10.1016/j.jvs.2005.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic versus conventional abdominal aortic aneurysm repair: A case-control study

Abstract: This case-control study provides preliminary results that short-term outcomes of total laparoscopic AAA repair are comparable with those of open surgery. Peroperative data demonstrate that laparoscopy is more technically demanding than open repair. However, the technical challenge of laparoscopy does not worsen the postoperative course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 21 publications
4
44
0
4
Order By: Relevance
“…Some studies have shown that the time to first flatus is 2-3 PODs and the time to resuming a diet is 4-8 PODs following transperitoneal abdominal aortic surgery [6,9,10,17]. Similar to previous reports, the number of days to first flatus and to resuming food intake was 2.35 and 3.86 days, respectively, in our control group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some studies have shown that the time to first flatus is 2-3 PODs and the time to resuming a diet is 4-8 PODs following transperitoneal abdominal aortic surgery [6,9,10,17]. Similar to previous reports, the number of days to first flatus and to resuming food intake was 2.35 and 3.86 days, respectively, in our control group.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, reports indicate that early oral intake does not reduce the duration of postoperative ileus or increase the rate of nasogastric tube reinsertion significantly [6]. Minimally invasive surgery, such as minilaparotomy, laparoscopic procedures, and endovascular surgery, may lead to earlier recovery of postoperative bowel function and shorter hospital stays, because of reduced tissue trauma [7][8][9][10][11]. However, minimally invasive techniques are not available for all surgical procedures and we must devise new surgical techniques to address these issues.…”
Section: Introductionmentioning
confidence: 99%
“…However, the greater part of this procedure consists of the laparoscopic dissection of the abdominal aorta. From our search into the ''best'' approach, and because of the technical challenge of this advanced laparoscopic procedure (e.g., control of bleeding [6]), we have yet to complete our learning curve for the laparoscopic part of this procedure before a considerable drop in operative time can be anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Hiromatsu and colleagues established that those patients with a skin incision of less than 15cm had a significantly smaller incidence of ileus when compared to a group of patients that had a skin incision of greater than 20cm (Hiromatsu et al, 2007). Laparoscopic repair has also demonstrated a shorter period of ileus and a quicker return to diet when compared to open repair (Coggia et al, 2005).…”
Section: Risk Factorsmentioning
confidence: 99%